Human CLEC9A antibodies deliver NY-ESO-1 antigen to CD141+ dendritic cells to activate naïve and memory NY-ESO-1-specific CD8+ T cells. Issue 2 (30th July 2020) - Masterman, Kelly-Anne; Haigh, Oscar L; Tullett, Kirsteen M; Leal-Rojas, Ingrid M; Walpole, Carina; Pearson, Frances E; Cebon, Jonathon; Schmidt, Christopher; O'Brien, Liam; Rosendahl, Nikita; Daraj, Ghazal; Caminschi, Irina; et al.
Abstract : Background: Dendritic cells (DCs) are crucial for the efficacy of cancer vaccines, but current vaccines do not harness the key cDC1 subtype required for effective CD8 + T-cell-mediated tumor immune responses. Vaccine immunogenicity could be enhanced by specific delivery of immunogenic tumor antigens to CD141 + DCs, the human cDC1 equivalent. CD141 + DCs exclusively express the C-type-lectin-like receptor CLEC9A, which is important for the regulation of CD8 + T cell responses. This study developed a new vaccine that harnesses a human anti-CLEC9A antibody to specifically deliver the immunogenic tumor antigen, NY-ESO-1 (New York esophageal squamous cell carcinoma 1), to human CD141 + DCs. The ability of the CLEC9A-NY-ESO-1 antibody to activate NY-ESO-1-specific naïve and memory CD8 + T cells was examined and compared with a vaccine comprised of a human DEC-205-NY-ESO-1 antibody that targets all human DCs. Methods: Human anti-CLEC9A, anti-DEC-205 and isotype control IgG4 antibodies were genetically fused to NY-ESO-1 polypeptide. Cross-presentation to NY-ESO-1-epitope-specific CD8 + T cells and reactivity of T cell responses in patients with melanoma were assessed by interferon γ (IFNγ) production following incubation of CD141 + DCs and patient peripheral blood mononuclear cells with targeting antibodies. Humanized mice containing human DC subsets and a repertoire of naïve NY-ESO-1-specific CD8 + T cells were used to investigate naïve T cell priming. T cell effector function was measured by expression of IFNγ, MIP-1β, tumor necrosis factor and CD107a and by lysis of target tumor cells. Results: CLEC9A-NY-ESO-1 antibodies (Abs) were effective at mediating delivery and cross-presentation of multiple NY-ESO-1 epitopes by CD141 + DCs for activation of NY-ESO-1-specific CD8 + T cells. When benchmarked to NY-ESO-1 conjugated to an untargeted control antibody or to anti-human DEC-205, CLEC9A-NY-ESO-1 was superior at ex vivo reactivation of NY-ESO-1-specific T cell responses in patients with melanoma. Moreover, CLEC9A-NY-ESO-1 induced priming of naïve NY-ESO-1-specific CD8 + T cells with polyclonal effector function and potent tumor killing capacity in vitro. Conclusions: These data advocate human CLEC9A-NY-ESO-1 Ab as an attractive strategy for specific targeting of CD141 + DCs to enhance tumor immunogenicity in NY-ESO-1-expressing malignancies.